1638d The psychosocial work environment, suicide and self-harm: results from a case control study. (24th April 2018) - Greiner, BA; Leitao, S; Larkin, C; Corcoran, P; Gallagher, J; Arensman, E
Abstract : Introduction: Research shows that suicides are more common among the unemployed and in certain occupations such as elementary occupations, agriculture, construction and health care. Little is known about the specific psychosocial determinants in the occupational environment. Methods: A case-control study using psychological autopsy method with multiple sources including information from coroners' reports, GPs and next-of-kin interviews in 133 consecutive cases of suicide and probable suicide compared with frequency-matched general practice controls (n=53). Psychosocial work factors encompassed decision latitude, work demands, job insecurity social support and social relations. Chi 2 and logistic regression modelling with adjustment for confounders and comparison with Central Statistics Office employment data. Results: Of the 133 cases, 22% had worked in construction and 30% were unemployed, an overrepresentation when compared to national employment data. Of those unemployed, 36% had worked in construction. Cases were more likely to be unemployed (11% versus 6%) than controls and have worked in construction (29% versus 17%) and in agricultural/fisheries (14% versus 6%). Controls had a significantly higher job decision latitude, higher social support and higher job security compared to cases. Additional comparisons with adjustment for confounding will be presented. Discussion: The results concerning decision latitude are in line with other research showing that workers in elementary jobs are more prone to suicide. The Irish construction sector has been highly affected by the recent economic recession with many layoffs and insecure jobs. The overrepresentation of this sector in the suicide cases and the finding of job insecurity being associated with suicide suggests that job loss but also the threat of job loss may be a precipitating factor to suicide. The results will inform Ireland's National strategy to reduce suicide 'Connecting for Life', which specifically highlights that prevention approaches should target priority groups, one of them being specific occupational groups.